Partnerships to Address School Safety through a Student Support Lens - Summer G. Woodside; Tamara Estes Savage; Nicole A. Stargell; Veronica L. Hardy; Whitney P. Akers; Ki Byung Chae; Cindy Locklear; Shenika J. Jones; Joshua A. Peele; Skyla D. Pryor (International Journal of School Social Work, 2022)
School safety is a primary concern of school leaders, employees, parents, and a variety of community stakeholders. Attempts to mitigate and prevent school safety concerns often focus on strategies around school climate assessment, emergency communication, school safety plan development, and school resource officer employment (U.S. DHS et al., 2018). Involvement of key stakeholders, such as school social workers, school counselors, and school-based mental health professionals is emphasized in creating and assessing school safety in a wholistic manner. This article provides an overview of a Trainings to Increase School Safety grant program that was implemented with public school stakeholders through partnerships between a university and five public school districts in the Southeastern North Carolina region.
Keywords: school safety; student support; school social work; school mental health